Results of dynamic monitoring of the spectrum of bacterial causes of acute urinary tract infections in children - H. O. Lezhenko; O. Ye. Pashkova; K. V. Samoylyk (Zaporozhye State Medical University, 2023)
The aim of the study: to explore in dynamics the structure of pathogens in children of Zaporizhzhia region with acute urinary tract infections and the possible changes in their antibiotic susceptibility. Materials and methods. We analysed results of urine culture in 439 children aged 4 to 18 years with acute urinary tract infection (293 patients in 2014-2016 and 146 patients in 2018-2020). Determination of bacterial species and susceptibility to antibiotics was performed on a bacteriological analyzer VITEK 2 COMPACT (bioMerieux, France) using AES software: Global CLSI-based + Phenotypic (2014, 2018) in accordance with CLSI and EUCAST tables. The coefficient of antibiotic resistance was additionally calculated for each isolate. Results. According to the analysis of bacteriological monitoring, it was found that in 2018-2020 compared to 2014-2016 among the causative agents of acute urinary tract infections in children, the role of gram-negative bacteria had raised due to increasing the proportion of Escherichia сoli and Proteus mirabilis. Gram-positive microflora has been represented by bacteria of the genus Enterococcus, in 2018-2020 in most samples was isolated Enterococcus faecium (28.1 %), in 2014-2016 among the representatives Enterococcus faecalis prevailed (38.9 %). The analysis of antibiotic resistance showed that in 2018-2020 the number of resistant strains of E. coli to amikacin increased 6.8 times to 2014-2016 (Р < 0.01) and there was a decrease in the sensitivity of Enterococcus to aminopenicillins from 91.4 % to 41.3 % (P < 0.01). Among bacteria of the genus Enterococcus the average values of the coefficient of resistance to antibiotics in 2018-2020 increased 3.75 times compared to 2014-2016 due to a 2.3-fold increase in the frequency of multidrug-resistant strains (P < 0.05). Conclusions. The obtained data are convincing evidence of the need for mandatory bacteriological examination of urine before antibacterial therapy to increase the effectiveness of therapeutic measures, prevention of the emergence and spread of antibiotic resistance. An increase in resistance of E. coli to amikacin and Enterococcus spp. to ampicillin does not allow the use of these drugs as empirical therapy of acute urinary tract infections in children.